THE EFFECT OF NUMBERED HEADS TOGETHER (NHT) COOPERATIVE LEARNING MODEL AND LEARNING INTEREST ON STUDENT LEARNING OUTCOMES IN ECONOMICS SUBJECT AT SMAN 11 WAJO, TAKKALALLA DISTRICT, WAJO DISTRICT - Riska Sari; Tuti Supatminingsih; Muhammad Hasan; Rahmatullah Rahmatullah; Nurjannah Nurjannah (JURNAL EDUSCIENCE, 2023)
This research is a pseudo-experimental research that aims to find out whether there is an influence of collaborative learning models and learning interests on the learning outcomes of economic  students in SMAN 11Wajo. The free variables in this study are collaborative learning models such as Numbered Heads Together (NHT)  and interest in learning, while the bound variables are students' economic learning outcomes. The population in this study consisted of a set of SMA Negeri  11 Wajo students, while the sample was Class XIIIS 1 as an experimental class of 26 students and Class XI IIS 2 as a control class of 26 students. The  research data was collected by carrying out  learning performance tests with materials on economic growth and economic development in the form of pre- and post-tests as well as questionnaires to measure the students' interest in learning. Data analysis techniques use tests for normality, tests for homogeneity, and t-tests.According to the results of the data analysis in the statistical t-test, there were significant values for the cooperative learning model Heads Numbered Together (NHT) type 0.307> 0.05 and the significant value of learning interest 0.242> 0.05, so the hypothesis test results showed that H0 was accepted and Ha was rejected. Therefore, it can be concluded that there is no significant impact between the Numbered Heads Together (NHT) collaborative learning model and  interest in learning on the learning outcomes of economic  students in SMAN 11 WAJO, Takkalalla District, Wajo Regency, returns.Keywords: Numbered Heads Together (NHT), Interest In Learning, Learning Outcomes.AbstrakPenelitian adalah penelitian eksperimen semu yang dirancang demi mendeteksi apakah model pembelajaran kooperatif tipe Numbered Heads Together (NHT) dan minat belajar berpengaruh terhadap hasil belajar ekonomi siswa di SMAN 11 Wajo. Variabel bebas pada penelitian ini merupakn model pembelajaran kolaboratif tipe NHT serta minat belajar, untuk variabel terikat yaitu hasil belajar ekonomi siswa. Populasi dalam penelitian ini sejumlah siswa SMA Negeri 11 Wajo, sedangkan sampelnya merupakan Kelas XI IIS 1 untuk kelompok eksperimen sebanyak 26 siswa  serta kelas XI IIS 2 untuk kelompok kontrol sebanyak 26 siswa. Pengumpulan data penelitian dilaksanakan  dengan melakukan tes kinerja pembelajaran terhadap materi pertumbuhan ekonomi dan pembanguand ekonomi berupa pretest serta posttest dan kuesioner agar menetahui tingkat minat belajar. Teknik analisis data dilakukan dengan pengujian normalitas, homogenitas, serta uji-t. hasil analisis data pada uji-t statistik, nilai Sig. untuk NHT sebanyak 0,307>0,05 serta nilai Sig. untuk minat belajar  yaitu 0,242>0,05 sehingga hasil uji hipotesis menyatakan bahwa H0 diterima serta Ha ditolak. Dengan demikian diperoleh bahwa tidak terdapat pengaruh yang signifikan antara model pembelajaran kooperatif Numbered  Heads Together (NHT) dan minat belajar  terhadap hasil belajar siswa mata pelajaran ekonomi pada SMAN 11 WAJO, Kecamatan Takkalalla, Kabupaten Wajo.Kata kunci: Numbered Heads Together (NHT), Minat Belajar, Hasil Belajar.